LEGAL PROTECTION AGAINST VICTIMS OF SEXUAL HARASSMENT UNDER LAW NO. 12 OF 2022 CONCERNING CRIMINAL ACTIONS OF SEXUAL VIOLENCE - RAHMAT, DIDING (LEX LAGUENS: Jurnal Kajian Hukum dan Keadilan, 2024)
This research discusses legal protection for victims of sexual harassment based on Law no. 12 of 2022 concerning Crime of Sexual Violence.“Legal protection is an effort to provide security and recovery for victims. This law stipulates the rights of victims, including the right to treatment, protection and recovery. In addition, this research examines the prevention efforts that need to be taken to reduce the number of sexual harassment. The method used is normative juridical research. The research results show that collaboration between government, society and related institutions is very important in creating a safe environment for women and children. It is hoped that the implementation of comprehensive laws will provide better protection for victims and reduce the number of sexual harassment cases.”